The First Case Report of Endocarditis Caused by - Valerie Espinoza MS; Michael Valdez MD; Serghei Burcovschii MD; Isabel Fong PharmD, BCIDP, AAHIVP; Greti Petersen MD, FACP; Arash Heidari MD, FACP (SAGE Publishing, 2021)
The cases of human infections caused by Serratia fonticola are relatively rare. The few cases that have been reported primarily describe skin and soft tissue, urinary, and biliary tract infections. We describe a case of a 59-year-old man with infected bilateral lower extremity wounds who developed endocarditis due to S fonticola confirmed with transesophageal echocardiogram. The patient was treated with 6 weeks of antibiotic therapy and had an uneventful recovery. After a thorough review of the literature using PubMed and Google Scholar, we concluded that this is the first reported case of endocarditis caused by S fonticola .